Surviving a Feminized Profession: An Insight into Why Men Choose to Stay in Teaching - Joseph, Stephen - (Advances in Social Sciences Research Journal, 2015)
ABSTRACT This study explored the plight of men operating in a highly feminized teaching profession and examined several reasons why they chose to remain in the classroom. In a random sample, 709 male teachers from the northern and southern parts of Trinidad were selected to participate in the study. A mixed-method research design was employed aimed at triangulating quantitative and qualitative data obtained from a survey questionnaire and focus group discussions. Findings of the study revealed that the majority of male teachers (94%) remained in the classroom because of what they described as their passion for teaching, and 96% of the respondents perceived of themselves as positive role models for young boys. Results of this study show that perhaps the time has come for us to re-examine the argument about men serving as role models for boys in the context of the Caribbean classroom. The results also have implications for education policy decision making aimed at not only retaining existing teachers but also attracting and recruiting new male teachers into the Trinidad and Tobago school system. Keywords: male teachers, feminized teaching profession, male role models